Application of New Compositional Simulation Approach to Model Gravity Segregation In Volatile Oil Reservoirs - Ego Syahrial (Testing Center for Oil and Gas LEMIGAS, 2010)
In this paper, we investigate the recovery performance of gas injection from volatile oilreservoirs. Cross-sectional reservoir studies for investigating the gravity segregation duringdepletion and gas cycling in volatile oil reservoirs is discussed. Furthermore the effectsof vertical permeability on gravity segregation in a homogeneous and horizontal reservoirsare investigated.A new efficient compositional simulation approach was used in this study to investigatethe influence of gravity segregation and their magnitude in the case of lean gas injectioninto a volatile oil reservoir. The new compositional simulation approach was validatedthrough analytical and numerical methods, and it is unconditionally stable and as stableas fully compositional model.The results show that an increase in vertical to horizontal permeability ratios results inan increase in the effect of gravity segregation and yield early gas breakthrough. On theother hand, the smaller the permeability ratios (vertical to horizontal), better are the recoveriesdue to resulting even layer sweeps. Gravity forces have a considerable effect onvolatile oil recovery via gas injection and the need for determining not only the fluidcharacteristics but also the reservoir heterogeneities was significant.